Methods in Contemporary Linguistics - Leemann, Adrian; Ender, Andrea (De Gruyter Mouton, 2012)
The present volume is a broad overview of methods and methodologies in linguistics, illustrated with examples from concrete research. It collects insights gained from a broad range of linguistic sub-disciplines, ranging from core disciplines to topics in cross-linguistic and language-internal diversity or to contributions towards language, space and society. Given its critical and innovative nature, the volume is a valuable source for students and researchers of a broad range of linguistic interests.
Description based on print version record.
KU Select 2017: Backlist Collection
Keywords: Language Arts & Disciplines / Linguistics; Language arts; Electronic books